Controlled trial of an ankle support (Malleotrain) in acute ankle injuries. Issue 3 (September 1992) - O'Hara, J; Valle-Jones, J C; Walsh, H; O'Hara, H; Davey, N B; Hopkin-Richards, H; Butcher, R M
Abstract : A randomized, controlled parallel-group trial has assessed 14 days' use of a new ankle support (Malleotrain, Bauerfeind, Aldershot, UK) in 220 patients (118 Malleotrain, 102 control group) with acute ankle injuries. Self-assessed pain levels were significantly lower in the group using Malleotrain at the end of the trial (P less than 0.05), as were median times taken for reduction of symptom scores to 10% (P less than 0.05) and total analgesic consumption during the trial (P less than 0.05). Overall clinical assessment scores were significantly superior in the Malleotrain group (P less than 0.02). Of those patients who received Malleotrain, 112 of 116 patients who commented (95% of all Malleotrain-treated patients) did so positively and only one patient stopped wearing the support during the trial. Malleotrain is acceptable to patients with acute ankle injuries and its use increases the rate of alleviation of symptoms. Its use should therefore be considered in the management of all such patients.